--| home | txt | code | teach | talks | specialfunctionswiki | timescalewiki | hyperspacewiki | links |--
Back to the class

Define the function $p_n(t)=(-1)^n (-t)_n$.
1. Calculate $p_3(2)$.
Solution: Calculate $$\begin{array}{ll} p_3(2) &= (-1)^3 (-2)_3 \\ &= (-1) [(-2)(-1)(0)] \\ &= 0. \end{array}$$ 2. Calculate $p_2(3)$.
Solution: Calculate $$\begin{array}{ll} p_2(3) &= (-1)^2 (-3)_2 \\ &= 1[(-3)(-2)] \\ &= 6. \end{array}$$ 3. Calculate $p_4(3)$.
Solution: Calculate $$\begin{array}{ll} p_4(3) &= (-1)^4 (-3)_4 \\ &= 1[(-3)(-2)(-1)(0)] \\ &= 0. \end{array}$$

4. Calculate $\Delta p_3(t)$. Express your answer as a number multiplied to some $p_m(t)$.
Solution: Calculate $$\begin{array}{ll} \Delta p_3(t) &= p_3(t+1)-p_3(t) \\ &= (-1)^3(-(t+1))_3 - (-1)^3 (-t)_3 \\ &= (-1)^3 \left[ (-t-1)(-t)(-t+1) - (-t)(-t+1)(-t+2) \right] \\ &= (-1)^3 \left[ (-t)(-t+1) \right] \left[ (-t-1) - (-t+2) \right] \\ &= -\left[ (-1)^2 (-t)_2 \right] \left[ -3 \right] \\ &= 3 p_2(t) \end{array}$$ 5. Calculate $\Delta p_4(t)$. Express your answer as a number multiplied to some $p_m(t)$.
Solution: Calculate $$\begin{array}{ll} \Delta p_4(t) &= p_4(t+1)-p_4(t) \\ &= (-1)^4 (-(t+1))_4 - (-1)^4 (-t)_4 \\ &= (-1)^4 \left[ (-t-1)(-t)(-t+1)(-t+2) - (-t)(-t+1)(-t+2)(-t+3) \right] \\ &= -\left[ (-1)^3 (-t)_3 \right] \left[ (-t-1) - (-t+3) \right] \\ &= - p_3(t) [-4] \\ &= 4p_3(t). \end{array}$$ 6. Do you notice a pattern developing for your answers to numbers 4 and 5? What is it?
Solution: For any $m=1,2,3,\ldots$, $$\Delta p_m(t) = mp_{m-1}(t),$$ i.e. this is some kind of a "discrete power rule".